Evaluating the impacts of lockdown duties on mental health of male police personnel in Eluru City, Andhra Pradesh - Mediboina, Anjali; Sarathy, Naidana Partha; Reshma Sri, Vemuri; Sree Lakshmi, Makaraju (International Journal Of Community Medicine And Public Health, 2023)
Background: The COVID-19 pandemic placed immense demands on frontline workers, including police personnel, who bore the responsibilities of maintaining public order during lockdowns. This study focused on male police officers in rural India, examining the mental health impact of their post-lockdown duties, which included enforcing pandemic-related measures. Methods: An analytical cross-sectional study was conducted among police personnel in Eluru, Andhra Pradesh. Data was collected through interviews, using the depression, anxiety, and stress scale-21 (DASS-21) to assess mental health. Demographic variables (age, marital status) and stimulant use (tea, coffee, and cigarettes) were analyzed for associations with mental health scores via ANOVA. Results: Among 70 participants, the majority were aged 25-30 (37%), married (61.4%), and consumed stimulants, primarily tea (84.3%). Overall, participants reported moderate stress (mean =8±4.1), while anxiety levels varied (mean =2.73±3.34), and depression was generally low (mean =0.17±0.66). Age, marital status and stimulant use were found to be significantly associated with subscale scores, 36-40 age groups more likely to report anxiety and stress. Married individuals were more likely to report depression and anxiety. Stimulant use was associated with all three subscales. Conclusions: This study revealed the mental health of rural male police personnel after COVID-19 lockdown duties. It emphasizes generational stress differences and the influence of stimulants. Stigma, masculine norms, and rural challenges may suppress depression and anxiety reporting. Policymakers should act on these insights, fostering mental health awareness and interventions for this vital workforce. Longitudinal studies are crucial for deeper understanding.